Peningkatan Keterampilan Menyimak Dan Penguasaan Kosakata Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Pada Siswa Kelas I Min 4 Solok - Yusna Devi, Wiwi; Muflihah, Nurul (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Listening skills are a vital foundation for language development, yet they are often overlooked in early grades, resulting in passive learners with limited vocabulary. This condition was also observed in 30 first-grade students at MIN 4 Solok. The study employed Classroom Action Research using the Kemmis & McTaggart model, applying the Numbered Heads Together (NHT) strategy in two cycles to enhance listening skills and vocabulary mastery. Data were collected through observation, performance tests, interviews, and documentation, then analyzed descriptively in both qualitative and quantitative ways. The findings indicate a significant improvement: student mastery increased from 33.3% in the pre-cycle to 60% in Cycle I and 86.7% in Cycle II. Beyond academic scores, students gained greater confidence, active participation, and the ability to apply new vocabulary in meaningful contexts. These results confirm that the NHT model is effective in fostering cooperative listening-based learning in early-grade classrooms.